Hartz IV and the Decline of German Unemployment: A Macroeconomic Evaluation - Brigitte Hochmuth; Britta Kohlbrecher; Christian Merkl; Hermann Gartner (Center for Economic Studies and Ifo Institute (CESifo), 2021)
This paper proposes a new approach to evaluate the macroeconomic effects of the “Hartz IV” reform, which reduced the generosity of long-term unemployment benefits. We propose a model with different unemployment durations, where the reform initiates both a partial effect and an equilibrium effect. We estimate the relative importance of these two effects and the size of the partial effect based on the IAB Job Vacancy Survey. Our approach does not hinge on an external source for the decline in the replacement rate for long-term unemployed. We find that Hartz IV was a major driver for the decline of Germany's steady state unemployment and that partial and equilibrium effect were nearly of equal importance. In addition, we provide direct empirical evidence on labor selection, one potential dimension of recruiting intensity.
Keywords: E24; E00; E60; 330; unemployment benefits reform; search and matching; Hartz reforms